Dropped Nucleus during Cataract Surgery in South India: Incidence, Risk Factors, and Outcomes. (4th May 2022) - Engelhard, Stephanie B.; Haripriya, Aravind; Namburar, Sathvik; Pistilli, Maxwell; Daniel, Ebenezer; Kempen, John H.
ABSTRACT: Purpose: To determine incidence, risk factors for, and outcomes of dropped nucleus (DN) during cataract surgery. Methods: This is a matched case–control study at the Aravind Eye Hospital in Madurai, India. Out of 184 consecutive DN cases, 171 were included. The case immediately preceding the DN case by the same surgeon served as matched concurrent control. The proportion of cataract surgeries with DN was calculated with a 95% confidence interval (CI). Conditional logistic regression was used to generate odds ratios for potential risk factors. Results: Among 415, 487 consecutive cataract surgeries, incidence risk of DN was 0.044% [95% CI 0.038%, 0.051%], or 0.44 per 1, 000 surgeries in 52 months. Significant preoperative risk factors were posterior polar cataract (adjusted odds ratio [aOR] 21.73, p = .003); suspected loose zonules (aOR 8.85, p < .001); older age (aOR 1.57, p = .001); and presence of diabetes mellitus (aOR 1.79, p = .03). Associated intraoperative complications included zonular dialysis (OR 34.49, p < .001), vitreous disturbance (OR 193.36, p < .001), and posterior capsule rent (OR 384.39, p < .001). Phacoemulsification and manual small incision cataract surgery did not significantly differ in DN incidence. DN most commonly occurred during nucleus removal (35.1%) or during/immediately following hydrodissection (24.0%). Visual outcomes of DN were worse than controls on average, but 51.9% achieved visual acuity 20/40 or better at 1 month. Conclusions: DN occurred rarely, with low absolute risk even when a strong risk factor was present. Nearly all cases followed posterior capsular rent or zonular dialysis, usually with observed vitreous loss. In spite of increased risk of postoperative complications in the DN group, the majority achieved favorable results.